β-Catenin Controls the Electrophysiologic Properties of Skeletal Muscle Cells by Regulating the α2 Isoform of Na+/K+-ATPase - Zhao, Congying; Yu, Yonglin; Zhang, Yi; Shen, Jue; Jiang, Lihua; Sheng, Guoxia; Zhang, Weiqin; Xu, Lu; Jiang, Kewen; Mao, Shanshan; Jiang, Peifang; Gao, Feng (Frontiers in Neuroscience, 2019)
β-catenin is a key component of the canonical Wnt signaling pathway. It has been shown to have an important role in formation of the neuromuscular junction (NMJ). Our previous studies showed that in the absence of β-catenin, the resting membrane potential (RMP) is depolarized in muscle cells and expression of the α2 subunit of sodium/potassium adenosine triphosphatase (α2NKA) is reduced. To understand the underlying mechanisms, we investigated the electrophysiologic properties of a primary cell line derived from mouse myoblasts (C2C12 cells) that were transfected with small-interfering RNAs and over-expressed plasmids targeting β-catenin. We found that the RMP was depolarized in β-catenin knocked-down C2C12 cells and was unchanged in β-catenin over-expressed muscle cells. An action potential was not released by knockdown or over-expression of β-catenin. α2NKA expression was reduced by β-catenin knockdown, and increased by β-catenin over-expression. We showed that β-catenin could interact physically with α2NKA (but not with α1NKA) in muscle cells. NKA activity and α2NKA content in the cell membranes of skeletal muscle cells were modulated positively by β-catenin. These results suggested that β-catenin (at least in part) regulates the RMP and action potential in muscle cells, and does so by regulating α2NKA.